Ortho-Perio Continuum: An Interdisciplinary Approach - Swati Punyatoya1 , Saurav Panda2 , Rinkee Mohanty3 , Rashmita Nayak4 , Anurag Satpathy4 , Abhaya Cha (Institute of Medico-legal Publications Pvt Ltd, 2020)
Orthodontic therapy is a combination of process which is related to move the malalligned teeth by correctingits position. There have been many dental cases where orthodontic tooth movement is assisted by periodontaltherapy and also the periodontal condition is improved by orthodontic therapy. This interdisciplinaryapproach is a symbiotic relation between the two. This review highlights the various orthodontic therapiesrequiring periodontal therapy for better outcome and vice-versa. Harmonious cooperation between theperiodontist and orthodontist would provide satisfactory outcome for the combined orthodontic periodontalproblems. The knowledge of this approach in the field of dentistry would help clinicians’ decide a betteroutcome in patient’s favour.